Formation of a protective layer during IEC(b) test of epoxy resin loaded with silica nanoparticles - Meichsner, Christian; Clark, Timothy; Groeppel, Peter; Winter, Benjamin; Butz, Benjamin; Spiecker, Erdmann (IEEE Transactions on Dielectrics and Electrical Insulation, 2012)
The erosion resistance of materials against partial discharges (PD) is a useful first indicator of their suitability for use as high voltage insulators. Epoxy resin-based composites loaded with different concentrations of silica nanoparticles were exposed to high voltage stress via an IEC(b) electrode. Laser scanning analysis was used to investigate the eroded volume and the erosion depth. The aged samples were investigated by transmission electron microscopy (TEM) analysis and scanning transmission electron microscopy (STEM), which show the formation of a protective layer of partially fused nanoparticles. The results suggest that improved erosion resistance against PD using the IEC(b) electrode is caused by the in situ formation of a protective layer consisting of sintered nanoparticles.

Protective Layer of Al2O3 Nanocomposites and Surface Composition after Electrical Stress - Meichsner, Christian; Clark, Timothy; Groeppel, Peter; Winter, Benjamin; Butz, Benjamin; Spiecker, Erdmann (IEEE Transactions on Dielectrics and Electrical Insulation, 2015)
The performance of nanocomposites for improved resistance to electrical discharges has resulted in increased interest in nano-loaded thermosetting resins. First assessments of the performance of new systems can be obtained by a plate-electrode construction according to IEC(b). Epoxy resins loaded with different amounts of spherical alumina particles were tested following this procedure and parameters such as erosion depth and standardized volume analyzed. Transmission electron microscopy (TEM) and a three-dimensional (3D) reconstruction using electron tomography were used to determine the particle size distribution. TEM analysis after preparation of the eroded samples indicates the advantages and disadvantages of using alumina nanoparticles to improve the erosion resistance and showed a novel effect of the surface-grafted polysiloxanes. A comparison with conventional nano-silica-loaded resins reveals that the lower sintering tendency of Al2O3 is important.
Keywords: Alumina; epoxy resin; erosion resistance; nanoparticles; transmission electron microscopy; electron tomography